Impact of cleaning corn on mycotoxin concentration, and conditioning temperature on pellet quality and nursery pig performance - Yoder, Ashton D. (Kansas State University, 2018)
Three experiments were conducted to analyze the average mycotoxin concentration that may be reduced by cleaning corn, and to determine how removing broken kernels may affect nursery pig growth performance. A fourth and fifth experiment evaluated pellet processing parameters and their effects on gelatinized starch, phytase stability, pellet quality, and nursery pig growth performance. In Exp. 1 and 2, corn was divided into twenty 150 kg runs then cleaned by mechanical sieving. Run were randomly assigned to 1 of 4 experimental treatments: 1) no screen 2) 12.7 mm screen, 3) 4.8 mm screen, and 4) 12.7 + 4.8-mm screen. Across both experiments, cleaning reduced (P < 0.05) aflatoxin and fumonisin concentration by an average of 26% and 42.5%, respectively, compared to the original uncleaned corn level. In Exp. 3, 360 nursery pigs were evaluated to determine the impact of cleaning or pelleting on growth performance. Treatments were arranged in a 2 × 3 factorial with corn type (uncleaned vs. cleaned) and feed form (mash vs. pelleted from either mill A or B). Neither cleaning corn nor pellet mill type affected (P > 0.19) nursery pig growth performance. Pelleting improved (P < 0.0001) G:F by 7.6% compared to mash diets. This improvement in G:F is consistent when pelleting diets, however pellet processing parameters can influence this improvement percentage. For these reasons, Exp. 4 was a 3 × 4 factorial design with 3 pellet mills (model 3016-4, 1000 HD, or CL-5, California Pellet Mill Co., Crawfordsville, IN), that produced samples collected at 4 locations (initial, post-conditioner, post-die, or post-cooler). Across each pellet mill, the greatest gelatinized starch increase (P < 0.05) was found post-pellet die, while phytase stability decreased (P < 0.05) by 70% after conditioning feed to 85˚C. This decrease led to substituting phytase in the diet for other sources of phosphorus for Exp. 5, which was a 2 × 3 factorial design plus a control, with pellet diameter (4.0 or 5.2 mm), conditioning temperature (low, medium, or high), and mash, created seven experimental treatments. Overall, neither the pellet diameter × conditioning temperature interaction, nor the main effects, affected (P > 0.06) nursery pig growth performance, even though pellet quality improved (P < 0.0001) when increasing conditioning temperature. These data suggest that cleaning is an effective method to legally reduce aflatoxin and fumonisin concentration, and that increasing conditioning temperature improves pellet quality, but neither impacts nursery pig growth performance.
Keywords: Mycotoxin; Conditioning temperature; Nursery pigsPelleting